Functional Movement Screen (FMS®): análise das capacidades dinâmicas em praticantes de diferentes modalidades - Boava, André Luis Couto [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Functional Movement Screen (FMS) is a routine assessment composed of seven movements that could report limitations or asymmetries in stability and mobility by evaluating injury incidence, detecting muscular imbalance and movement dysfunction. Thus, the aim of this study was to analyze the effects of different physical activities on dynamic and equilibrium capacities through an FMS test. The test was applied in three groups; Crossfit (CF), Weightlifting (W) and Sedentary (S), with 15 volunteers each. For a comparison between the groups, a one-way ANOVA was used with post-hoc Bonferroni considering the level of significance of p <0.05. The Sedentary group showed a lower score in FMS (13,3 ± 2,77), the weight lifters and the Crossfit group showed a higher score (16,6±1,4 and 19±1,64, respectively), considering 14 or less an indicative of injury score (10,22). Therefore, there was a significant difference between the Sedentary group and the other groups (P<0,01). In a partial assessment of functional movements, notorious differences were observed in the three groups: CF, W and S for Deep Squat, with p<0,01, In-line Lunge (p=0,03), Hurdle step (p=0,03), Trunk Stability Push-Up (p=0,001) and Rotary Stability (p=0,02). There was some difference between CF and S groups; only Active Straight Leg Raise and Shoulder Mobility did not show significant differences. Thus, those individuals who do not perform physical activities showed a lower score in FMS, exhibiting an increased risk of injuries. The study did not show bigger differences between the CF and W groups, in the total score of FMS there was no significant difference and in a partial evaluation only Deep Squat showed difference. Therefore, through an analysis of an FMS test, we can conclude that Crossfit training does not necessarily result in better movement patterns, stability and join mobility when compared to weight lifters

O presente estudo teve como objetivo analisar o efeito de diferentes atividades físicas nas capacidades dinâmicas e de equilíbrio por meio do teste de FMS®, que é composto por sete movimentos podendo identificar limitações ou assimetrias na estabilidade e mobilidade de cada indivíduo, avaliando o risco de lesões e previsibilidade de desempenho. O teste foi aplicado em três grupos, Crossfit (CF), Musculação (M) e Sedentários (S) com 15 participantes cada. Para uma comparação entre os grupos foi utilizada uma ANOVA oneway, com post-hoc de Bonferroni sendo adotado o nível de significância de p<0,05. O score total do FMS® apresentou pontuação média no grupo Sedentário de 13,3±2,77, no grupo Musculação de 16,6±1,4 e no grupo Crossfit de 19±1,64, considerando 14 ou menos uma pontuação indicativa de lesões (KIESEL et al. 2007; VECCHIO; GONDIM; ARRUDA, 2016). Houve diferença significativa do grupo Sedentário em relação aos outros grupos (P<0,01). Em uma análise fragmentada dos movimentos obtivemos diferença significativa entre CF, M e S no item agachamento profundo, com p<0,01, nos itens avanço em linha (p=0,03), passo com barreira (p=0,03), flexão (p=0,001) e estabilização rotacional (p=0,02), observamos diferença apenas entre os grupos CF e S. Portanto aqueles indivíduos que não realizam atividade física apresentaram um pior desempenho no FMS®, elevando os riscos de lesões. Não observamos diferenças entre o grupo CF e M na análise do score total não houve diferença significativa já na análise fragmentada apenas no item agachamento profundo. Sendo assim, por meio de uma análise do FMS®, podemos concluir que o Crossfit, não necessariamente, resulta em melhores padrões de movimentos, estabilidade e mobilidade articular quando comparado à Musculação
Functional Movement Screen (FMS®): analysis of dynamic capacities in different modalities
Keywords: Capacidade motora; Capacidade motora - Testes; Exercícios físicos; Ferimentos e lesões